Work Life Balance Among Married Female Nursing Employees In Hospital Industries With Special Reference To Nabh Accredited Hospital At Kottayam District - Kerala State - Nainu Pareekshith, Dr. N. Ajithkumar, (International Journal of Advanced Science and Technology, 2020)
The term “Work Life Balance” (WLB) is widely used across the globe in almost all the sectors. Efficient way of managing one’s Profession/work, Family and personal wellbeing determines the positive work life balance of an individual. Success of every organization depends on its employees. Organization has understood that they can positively influence its employees by creating inclusive Work Life Balance.Several studies show that when Work Life Balance is positive, an individual will be able to contribute his best towards the work, family and his/her self needs. Health industry in India is growing at swift pace and majority of the work forces are contributed by women. As per the NITI Aayog’s second edition of “Health States, Progressive India” report, Kerala as a state is one of the front-runners in Health sector as a whole. National Accreditation Board for Hospitals & Healthcare Providers (NABH) is a constituent board of quality control of India, set up to establish and operate accreditation programme for health care organization.Through this research paper, study was made on Work life balance of married female nurses working in NABH accredited hospitals at Kottayam district (Kerala State – India). Demographic factors mainly Age, Qualification, Experience and Number of Children were considered as Dependent variables and Work Life Balance as Independent Variable. All the three NABH accredited hospitals of Kottayam were considered for the study with the total sample size of 100 married female nurses.Questionnaire was used for data collection and first hand data were made for data analysis by using SPSS software with the help of multiple linear regression method and T - test. The association of the Dependent Variables were assessed with the Work life balance of the nurses. The results of the study showed that demographic factors like Qualification and Number of Children has a direct relationship with the work life balance of the nurses whereas Age and Experience has no association between the work life balance.